1942
DOI: 10.1002/path.1700540406
|View full text |Cite
|
Sign up to set email alerts
|

The growth of coliform bacilli in water containing various organic materials

Abstract: AN example of the growth of coliform bacilli in water containing organic material was recorded by Houston in 1916. The water from a tap on a pressure main in the Metropolitan Water Board's works gave very unsatisfactory bacterial counts, the cause of which was eventually traced to a leather washer. The " leather bacillus " which was isolated from the washer was indistinguishable from B. capszclatus and B. bctis acerogenes except for the production of indole. These two organisms increased in numbers when seeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1951
1951
1971
1971

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Histology of the cork suggests that organisms colonize the fissures in large numbers, and that dry, friable closures are particularly likely to produce infection in this manner. Although the experiments of Nelson (1942) demonstrate that cork extracts can allow the multiplication of coliform organisms in distilled water, the nutrients concerned do not appear in solutions with cork closures in sufficient concentration to be detected by chromatography. Contaminating organisms, however, can clearly multiply in the interstices of corks, since it is scarcely credible that the large numbers seen in sections could have arisen from direct implantation only.…”
Section: Infected Cork Closures Andmentioning
confidence: 98%
See 1 more Smart Citation
“…Histology of the cork suggests that organisms colonize the fissures in large numbers, and that dry, friable closures are particularly likely to produce infection in this manner. Although the experiments of Nelson (1942) demonstrate that cork extracts can allow the multiplication of coliform organisms in distilled water, the nutrients concerned do not appear in solutions with cork closures in sufficient concentration to be detected by chromatography. Contaminating organisms, however, can clearly multiply in the interstices of corks, since it is scarcely credible that the large numbers seen in sections could have arisen from direct implantation only.…”
Section: Infected Cork Closures Andmentioning
confidence: 98%
“…Experiment 2. To Exclude Growth Factors in Cetrimide Derived from Cork.-In view of the experimental findings of Nelson (1942), the cetrimide solution was examined for the presence of growth factors which might allow either survival or multiplication of contaminants. A portion of the solution was Seitz-filtered to remove organisms and examined by two-dimensional chromatography, using as solvent 80% alcohol and phenol saturated with water.…”
Section: Infected Cork Closures Andmentioning
confidence: 99%
“…pyocyanea will readily grow in culture media containing 10% and more of cetrimide suggests a mechanism by which organisms deposited on the corks of bottles may survive intermittent contact with this fluid. This explanation gains support from the observation of Nelson (1942), who isolated coliform bacilli from bottles of sterile distilled water, and showed that growth-promoting substances could be derived from cork. Deposited on moistened corks by contaminated fingers, Ps.…”
Section: Discussionmentioning
confidence: 63%